2013
DOI: 10.4103/2152-7806.120784
|View full text |Cite
|
Sign up to set email alerts
|

A blunt needle (Epimed®) does not eliminate the risk of vascular penetration during transforaminal epidural injection

Abstract: Background:Transforaminal epidural injection of local anesthetics and corticosteroids is a common practice in patients with radicular pain. However, serious morbidity has also been reported, which can be attributed to an arterial or venous injection of the medication especially particulate glucocorticoid preparations. Using a blunt needle in contrast to sharp needle has been suggested to reduce this risk in a study on animals.Case Description:We present a 59-year-old female with L5 lumbar radicular symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Clinical experience has shown that blunt needles do not offer good directionality and may prolong procedures. A case report in the literature has found that a blunt needle, negative aspiration, or a test dose of the local anesthetic does not offer reliable protection against vascular penetration [ 8 ]. However, in a retrospective study of 185 transforaminal epidural steroid injections, paresthesia was reported in three cases with blunt needles versus eight cases with a sharp needle.…”
Section: Reviewmentioning
confidence: 99%
“…Clinical experience has shown that blunt needles do not offer good directionality and may prolong procedures. A case report in the literature has found that a blunt needle, negative aspiration, or a test dose of the local anesthetic does not offer reliable protection against vascular penetration [ 8 ]. However, in a retrospective study of 185 transforaminal epidural steroid injections, paresthesia was reported in three cases with blunt needles versus eight cases with a sharp needle.…”
Section: Reviewmentioning
confidence: 99%
“…Whilst some of the evidence does suggest blunt needles may be safer, the first cases of spinal cord injury the use of blunt needles are now being reported to be associated with vascular spread [37] The curved, blunt RF (Racz-Finch) needle is being used increasingly in an attempt to avoid intraneural, intracord and intra-arterial placement especially with the use of particulate corticosteroids. Thus far, no cases involving these needles have surfaced.…”
Section: The Debate Over Sharp Versus Blunt Needlesmentioning
confidence: 99%